1998
DOI: 10.1023/a:1006011328655
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor negative and progesterone receptor positive primary breast cancer: Pathological characteristics and clinical outcome

Abstract: The expression of estrogen (ER) and progesterone (PgR) receptors was analyzed in a retrospective series of 3000 patients who had operable primary breast cancer. Patients were stratified according to ER and PgR status and the study was focused on the two groups (ER-PgR+ and ER-PgR-) of patients whose tumors contained low levels of ER (< 15 fmol/mg protein), regarding potential response to endocrine therapy. The comparison of clinical or histological characteristics between ER-PgR+ and ER-PgR- patients was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 17 publications
3
20
2
3
Order By: Relevance
“…In our study, the ER -/PgR + profile was a significantly unfavourable factor for the whole patient cohort both in univariate and in multivariate analysis. Interestingly, such a profile occurred in only 2% of patients in one large-scale study, based on 3000 breast cancer cases (29), while in our STS study this profile was seen in 14% of the tumors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In our study, the ER -/PgR + profile was a significantly unfavourable factor for the whole patient cohort both in univariate and in multivariate analysis. Interestingly, such a profile occurred in only 2% of patients in one large-scale study, based on 3000 breast cancer cases (29), while in our STS study this profile was seen in 14% of the tumors.…”
Section: Discussioncontrasting
confidence: 67%
“…Shortly, any hormone receptor positivity gives better prognosis for success of antihormonal therapy (29,30). We were not able to find any available published investigation of the prognostic impact of ER/PgR coexpression profiles on DSS and overall survival without relation to endocrine therapy.…”
Section: Discussionmentioning
confidence: 84%
“…Similar correlations have been seen between tumor invasiveness and low levels of hormone (10,11) or higher levels of receptor (12)(13)(14). The majority of breast cancers stain positively for both PGR and estrogen receptor; receptor positivity is predictive of response to tamoxifen and overall survival.…”
Section: Introductionsupporting
confidence: 58%
“…The frequency of ER¡/PgR+ tumors is about 2-7% in western breast cancer patients (Bernoux et al 1998;Grann et al 2005), 8% in Middle-East counterparts as reported (Kiani et al 2006). In present study of China, the proportion was up to 11%.…”
Section: Discussionmentioning
confidence: 49%